Morphological segmentation of remotely sensed forest covers in high spatial resolution images - Barata, T; Pina, P (MATHEMATICAL MORPHOLOGY, PROCEEDINGS, 2002)
In this paper novel algorithms developed to automatically segment forest cover types are presented. The digital image analysis followed is mainly based on mathematical morphology operators and exploits the textural features in high spatial resolution images. These input images consist of true colour digital orthophotos and the studied forest covers consist of the main occurrences in Portugal: olive trees, cork oak trees, pine and eucalyptus trees.
Keywords: forest covers; high spatial resolution images; segmentation; textural features

Characterization of cells in cork - Pina, P; FORTES, M A (JOURNAL OF PHYSICS D-APPLIED PHYSICS, 1996)
Various topological and metric properties of the cells in the phelogen of the cork oak have been measured in tangential sections of cork by image analysis methods. These include the fractions f(i) of cells with i sides (i-cells), the fractions f(ik), of adjacencies between i- and k-cells and various distributions of cell areas in relation to topology.